Physicochemical And Functional Properties Of Mango Seed Dietary Fiber Extract (Msdfe), Papaya Seed Dietary Fiber Extract (Psdfe) And Honeydew Seed Dietary Fiber Extract (Hsdfe) - Lim, Siew Guan (Universiti Sains Malaysia, 2020)
Fruit seeds were previously discarded as waste, which could lead to environmental pollution and loss of valuable biomass. Recent research, however, has indicated that the seeds may have potential use as dietary fiber (DF) source and important ingredient of a healthy diet. In this research, DF was extracted from mango, papaya and honeydew seeds and the optimum extraction conditions were determined. All fruit seeds showed maximum DF extraction yield when extraction was conducted at 80 °C for 3 h using 3% NaOH at a liquid-solid ratio of 15:1. The nutritional composition, pH value and some physical and functional properties of the extracted DF were then examined. Analyses revealed that all DF extracts exhibit low moisture, fat, ash and protein contents and present high amounts of total sugar, starch and total dietary fiber (TDF). Of the three DF extracts, mango seed dietary fiber extract produced the highest amounts of starch (28.68 g/100 g dry extract) and total sugar (41.77 g/100 g dry extract) whilst honeydew seed dietary fiber extract (HSDFE) revealed the highest TDF content (81.96 g/100 g dry extract). A great difference in the ratio of insoluble dietary fiber (IDF) to soluble dietary fiber contents was found in papaya seed dietary fiber extract and HSDFE. Besides slightly acidic and low bulk density, all DF extracts were yellowish in colour and showed high water holding (WHC), water swelling (WSC) and oil holding capacities (OHC).